(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Domestic tourism is an excellent opportunity to learn more about Uzbekistan, traveling through the most diverse and unique natural, historical, archaeological, ethnographic and iconic cultural attractions, go on an unforgettable journey to attractive places of antiquity, relax surrounded by pristine nature.